Węgierska parodia filmowa. Skutki uboczne parodii filmowych z czasów Kádára - Hučko, Tomáš (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
In the rich and colorful Hungarian film history from post-war years to the present day we find an abundance of comedies combining satire, epigram, burlesque, but true parody film among them is not too much, is a rare phenomenon. What is the reason? We are looking for the answers in examples of two trials of parody film: the first and the only parody of James Bond: Az Oroszlan ugrani készül (dir. György Révész, 1969) and Kojak Budapesten (dir. Sándor Szalkai,1980), inspired by the main character of the American television series Kojak. Both attempts are accompanied with specific “side effects”. It tells a lot about the possibilities and limits of the Hungarian film parody.